"It's Wrong to Exclude Girls From Something They Love." Adolescents' Attitudes About Sexism in Science, Technology, Engineering, and Math. Issue 1 (9th November 2018) - Robnett, Rachael D.; John, Jennifer E.
Abstract : The current research examined adolescents' attitudes about sexism in fields related to science, technology, engineering, and math (STEM). The ethnically diverse sample (61% East Asian) was composed of 629 adolescents ( M age = 16.09) who attended a public school in the United States. Participants responded to closed‐ and open‐ended questions about the prevalence and severity of sexism in STEM. We used latent profile analysis to classify participants into latent classes according to their responses. Of note, one latent class included participants who perceived sexism in STEM as a fairly common and very serious problem. Relative to the other classes, participants in this class were more likely to be girls and showed higher STEM value. Qualitative analyses illustrated that the participants in each class reasoned in fundamentally different ways about sexism in STEM.